2012
DOI: 10.17221/393/2010-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Formulation, physicochemical, nutritional and sensorial evaluation of corn tortillas supplemented with chía seed (Salvia hispanica L.)

Abstract: Rendón-Villalobos R., Ortíz-Sánchez A., Solorza-Feria J., Trujillo-Hernández C.A. (2012): Formulation, physicochemical, nutritional and sensorial evaluation of corn tortillas supplemented with chía seed (Salvia hispanica L.). Czech J. Food Sci., 30: 118-125.Composite flours containing 5%, 10%, 15%, and 20% of chia seed flour and corn were used for tortilla formulations. The effects of chia powders supplementation on the physicochemical and sensorial characteristics as well as starch digestibility of the tortil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 34 publications
3
31
0
2
Order By: Relevance
“…With the increase in the quantity of chiaseed in composite flour, the moisture content decreased. Similar results were reported by Rendón‐Villalobos, Ortíz‐Sánchez, Solorza‐Feria, and Trujillo‐Hernández () who prepared tortilla by adding different quantity of chiaseeds. This decrease in moisture content may be the result of hydrophobic properties of fat present in chiaseeds (Villalobos, Acevedo, Diaz, Tovar, & Pérez, ).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…With the increase in the quantity of chiaseed in composite flour, the moisture content decreased. Similar results were reported by Rendón‐Villalobos, Ortíz‐Sánchez, Solorza‐Feria, and Trujillo‐Hernández () who prepared tortilla by adding different quantity of chiaseeds. This decrease in moisture content may be the result of hydrophobic properties of fat present in chiaseeds (Villalobos, Acevedo, Diaz, Tovar, & Pérez, ).…”
Section: Resultssupporting
confidence: 87%
“…This shows that with the increase of chiaseeds the ash content of product increased. A similar trend in ash content was observed in tortilla prepared with different levels of chiaseeds (Rendón‐Villalobos et al, ). According to the statistical results, the ash contents of chiaseed‐ and coconut powder‐enriched flaxseed balls differed considerably within the treatments.…”
Section: Resultssupporting
confidence: 79%
“…A study by Sandoval‐Oliveros and Paredes‐Lopez () has shown that proximate composition of chia seeds is in agreement with our results. Rendon‐Villalobos and others () have demonstrated that the addition of chia seeds had a very positive effect on nutritional properties, specifically levels of proteins, lipids, and total dietary fibers in the prepared corn tortillas.…”
Section: Resultsmentioning
confidence: 98%
“…In 2000, the US Dietary Guidelines recommend that chia seed can be used as a primary food not exceeding 48 g/day. Chia is commonly consumed as salad from chia sprout, in beverages, cereals, and salad dressing from the seed, or it is eaten raw [41, 42]. The European Commission approved the use of chia seed in bread products with a limit of not more than 5%.…”
Section: Market Potential and Commercial Application Of Chia Seedmentioning
confidence: 99%